2020
DOI: 10.1017/9781108907552
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about Animals in Thirteenth-Century Paris

Abstract: This book seeks to understand what masters of theology at the University of Paris in the thirteenth century had to say about similarities and differences between humans and animals. It explores the ways in which they related similarities and differences to each other, holding them in productive tension, so as to construct a boundary between humans and animals, or to query and blur such a boundary. In recent years some wonderful work has been published on the representation of animals in the vernacular literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Though many thinkers did subscribe to the notion that nonhumans are incapable of reason, Oelze (2018) has demonstrated that the mediaeval debate about this topic was nuanced and complex as several thinkers did believe that nonhumans were capable of certain rational processes, such as reasoning, judging, or employing prudence. Likewise, Wei (2020) has recently argued that Parisian theologians enjoyed considerable freedom in exploring the boundary between humans and nonhumans as they saw fit, provided that they acknowledged humankind's unique capacity for reason. He observes that there was "tremendous diversity and creativity in the strategies that they adopted for making sense of similarities in relation to difference, for holding similarity and difference in productive tension" (pp.…”
Section: The Properties Of Things 24mentioning
confidence: 99%
“…Though many thinkers did subscribe to the notion that nonhumans are incapable of reason, Oelze (2018) has demonstrated that the mediaeval debate about this topic was nuanced and complex as several thinkers did believe that nonhumans were capable of certain rational processes, such as reasoning, judging, or employing prudence. Likewise, Wei (2020) has recently argued that Parisian theologians enjoyed considerable freedom in exploring the boundary between humans and nonhumans as they saw fit, provided that they acknowledged humankind's unique capacity for reason. He observes that there was "tremendous diversity and creativity in the strategies that they adopted for making sense of similarities in relation to difference, for holding similarity and difference in productive tension" (pp.…”
Section: The Properties Of Things 24mentioning
confidence: 99%